Indonesia's Digital Education Revolution: Enhancing Vocational Learning Through Technology-Driven Project-Based Methods - Akhtar, Rana Sharjeel; Imleesh, Mohammed Mahmoud Mohammed (Universitas Veteran Bangun Nusantara, 2025)
Indonesia is undergoing a transformative era in vocational education, pushed by the integration of technology-driven, project-based learning (PJBL) methodologies and Learning Management Systems (LMS). This comprehensive study examines the implementation and effectiveness of technology-driven project-based learning at SMK Cut Nya' Dien, utilizing a quasi-experimental design with 35 students divided into experimental and control groups. Using SPSS statistical analysis, the research demonstrates significant improvements in student learning outcomes, creativity measures, and engagement levels in the experimental group that utilized Google Classroom LMS with project-based learning approaches. This study is contributing to the growing body of literature supporting the efficacy of technology-integrated pedagogical methods in vocational education settings, providing empirical evidence for policy makers and educational practitioners seeking to enhance graduate employability and industry alignment. Results revealed statistically significant differences between groups (t (33) = 4.852, p = 0.0003) with a very large effect size (Cohen's d = 1.67), indicating substantial practical significance for educational implementation.